Quantitative Structure-Retention Relationship Modelling of Aroma Components in Fenjiu, China - Qiao, Hua; Feng, Li; Sun, Tijian (Asian Journal of Chemistry, 2013)
Aroma compounds are very important for identification and quality control of liquors and prediction of the retention times of given aroma compounds can be a useful method for characterizing liquors. In this paper, Fenjiu was analyzed by using gas chromatography-mass spectrometry without pretreatment. Quantitative structure-retention relationship models were constructed by various molecular descriptors of identified aroma compounds. These models show high correlation coefficients and low standard errors. To test the predictive quality of the quantitative structure-retention relationship models, leave-one-out cross validation technique was employed. Results indicate that the models are of good predictive quality.